Capabilities of global high-level isolation units: A pre-workshop survey. (1st November 2022) - Herstein, Jocelyn J.; Wolf, Timo; Nicastri, Emanuele; Leo, Yee Sin; Lim, Poh Lian; Jacobs, Michael; Vanairsdale, Sharon; Toner, Eric; Shearer, Matthew P.; Vasa, Angela; Mukherjee, Vikram; Echeverri, Andrea; et al.
Abstract: Objective: To assess experience, physical infrastructure, and capabilities of high-level isolation units (HLIUs) planning to participate in a 2018 global HLIU workshop hosted by the US National Emerging Special Pathogens Training and Education Center (NETEC). Design: An electronic survey elicited information on general HLIU organization, operating costs, staffing models, and infection control protocols of select global units. Setting and participants: The survey was distributed to site representatives of 22 HLIUs located in the United States, Europe, and Asia; 19 (86%) responded. Methods: Data were coded and analyzed using descriptive statistics. Results: The mean annual reported budget for the 19 responding units was US484, 615. Most (89%) had treated a suspected or confirmed case of a high-consequence infectious disease. Reported composition of trained teams included a broad range of clinical and nonclinical roles. The mean number of HLIU beds was 6.37 (median, 4; range, 2–20) for adults and 4.23 (median, 2; range, 1–10) for children; however, capacity was dependent on pathogen. Conclusions: Responding HLIUs represent some of the most experienced HLIUs in the world. Variation in reported unit infrastructure, capabilities, and procedures demonstrate the variety of HLIU approaches. A number of technical questions unique to HLIUs remain unanswered related to physical design, infection prevention and control procedures, and staffing and training. These key areas represent potential focal points for future evidence and practice guidelines. These data are important considerations for hospitals considering the design and development of HLIUs, and there is a need for continued global HLIU collaboration to define best practices.